2011
DOI: 10.1088/0954-3899/38/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic wave equations ofn-body systems of particles and antiparticles of various masses in scalar quantum field theory

Abstract: A generalization of the scalar Yukawa model to include many 'flavors' of scalar particles and antiparticles is considered. The variational method within the Hamiltonian formalism of quantum field theory is used to derive relativistic n-body wave equations for stationary systems consisting of scalar particles and antiparticles where all the particles and antiparticles have different masses. Using a simple ansatz we derive the relativistic n-body wave equations for any n integer number. The equations are shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…of the non-relativistic limit of eq. ( 31), is as expected, the n-body Schrödinger equation, (35) where…”
Section: Qed N-body Wave Equationssupporting
confidence: 74%
See 2 more Smart Citations
“…of the non-relativistic limit of eq. ( 31), is as expected, the n-body Schrödinger equation, (35) where…”
Section: Qed N-body Wave Equationssupporting
confidence: 74%
“…No (approximate) solutions of the relativistic four-fermion equation (47) have been obtained to date. The non-relativistic limit of (47) is, of course, equation (35) with n = 4.…”
Section: Two Three and Four-body Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of six-body system, for particles only and no virtual annihilation interaction [5], was done before and it has been included in the Tables 3 and 4 as well as the calculation of the case of combined three particles and three antiparticles with virtual annihilations and with retardation effects [9]. The corresponding graphs are also put in Fig.…”
Section: ð3:7þmentioning
confidence: 99%
“…In previous works by EmamiRazavi [5,6], it has been demonstrated that, by employing a reformulated model in QFT proposed by Darewych [7,8], formulas concerning relativistic n-body wave equations for scalar particles and/or antiparticles can be obtained (see also [9]). It has also been proven that using Darewych's formalism [7,8] relativistic n-fermion wave equations (particles and antiparticles; spin-1/2) in quantum electrodynamics can be obtained [10,11].…”
Section: Introductionmentioning
confidence: 99%